Method for developing sprout of food crops - ZHONG, TIAN-JING (2006)
The present invention relates to a method for sprout-developing of food crops, especially to a method for promoting grain germination by providing high oxygen, comprises pre-treating, soaking and culturing process in the initial stage. During the sprout development stage, energy water is sprinkled and motive energy is performed simultaneously to provide the sprout with adequate oxygen and life energy stimulation. In this procedure, enzymes can be induced to catalyze the development factors to produce new life, and active rice having life energy is produced.